Effect of egg white and its hydrolysate on stearoyl-CoA desaturase index and fat accumulation in rat tissues. (December 2014) - Ochiai, Masaru; Matsuo, Tatsuhiro
Abstract We investigated the dietary effects of egg white (EW) and its hydrolysate (EWH) on fat metabolism in rats. Wistar rats were divided into casein, EW and EWH dietary groups, and fed their respective diet for 8 weeks. Dietary EW and EWH decreased food intake, body weight gain and fat accumulation in the carcass, liver, muscles and adipose tissues, but muscle weight was increased. In addition, dietary EW and EWH decreased stearoyl-CoA desaturase (SCD) indices and glucose-6-phosphate dehydrogenase activity of the liver and gastrocnemius muscle. Dietary EW also increased the fecal excretion of triacylglycerol, cholesterol and total bile acids, and decreased the serum levels of triacylglycerol and leptin. The suppressive effects of dietary EW on food intake and body fat accumulation were weakened by dietary EWH. These findings indicate that EW and EWH, especially EW, are effective in reducing body fat accumulation by regulating hepatic and muscular SCD indices.